School of Virtues: dancing in 19th century São Paulo (decades of 1830-1860) - Victor Andrade Melo; Flávia da Cruz Santos (Universidade Federal do Rio Grande do Sul, 2018)
The purpose of this study is to discuss the experiences with dance promoted in São Paulo between the 1830's and 1860's, mainly the discourses that considered them as school of virtues, strategies to educate considering new social requirements that were outlined in a city. It is, therefore, an investigation on initiatives of body education, here understood as a broad process of adaptation to new customs, something that involves corporal techniques as well as certain behaviours. The study period consider the first initiatives of structured teaching of the dance and the beginning of the moment in which there was a great development of São Paulo. As sources, they were used periodicals published in the period.